Detection of immunoglobulins and complement components in formalin fixed and paraffin embedded renal biopsy material by immunoflourescence technique - Muhammed Mubarak; Javed I Kazi; Umme Kulsoom; Muhammed Ishaque (Society of Diabetic Nephropathy Prevention, 2012)
Background: The technique of direct immunoflourescence (IF) is essential in the accurate diagnosis of renal glomerular diseases. The optimal results are obtained when the procedure is done on fresh frozen tissue (IF-F). However, techniques are available for IF study on formalin fixed and paraffin embedded (FFPE) renal biopsy specimens with variable reported success rates. Objectives: We evaluated three such techniques on FFPE tissue and compared the results with those obtained by IF-F from the same patients. Materials and Methods: Heat treatment with Tris buffer and citrate buffer, and pronase treatment of the FFPE material was carried out. Direct IF was done for renal panel immunoglobulins and complement components on all biopsies and the results were compared with the historical IF-F study. Results: When compared to the IF-F, the immunoflourescence staining on the paraffin sections was less sensitive and less intense in all immune complex-mediated renal diseases, but the diagnostic findings were detected in majority of the cases. Conclusions: In conclusion, it is possible to establish the diagnosis in most cases of immune complex-mediated glomerular diseases with IF on paraffin embedded tissue specimens.